Evaluating the bioequivalence and safety of liraglutide injection versus Victoza® in healthy Chinese subjects: a randomized, open, two-cycle, self-crossover phase I clinical trial - Liu, Chao; Xu, Hongrong; Yuan, Fei; Chen, Hanjing; Sheng, Lei; Chen, Weili; Xie, Haisong; Xu, Hongmei; Li, Xuening (Frontiers in Pharmacology, 2023)
Background: Liraglutide is an acylated glucagon-like peptide-1 (GLP-1) analog, and its pharmacokinetic and pharmacodynamic properties as a GLP-1 receptor (GLP-1R) agonist make it an important therapeutic option for many patients with type 2 diabetes mellitus. This study compared the bioequivalence and safety of liraglutide with the originator product in healthy Chinese adult subjects. Methods: Subjects (N = 36, both sexes) were randomized in a 1:1 ratio into two groups (18 cases each) for a two-cycle, self-crossover trial. Each cycle involved a single subcutaneous injection of the test and reference drugs, with a washout period of 14 days. The plasma drug concentration was quantified by liquid chromatography-tandem mass spectrometry (LC-MS/MS). The main pharmacokinetic parameters were statistically analyzed to assess drug bioequivalence. Furthermore, the safety of the drugs was assessed throughout the trial. Results: The geometric mean ratios of Cmax, AUC0-t, and AUC0-∞ were 103.73%, 103.01%, and 103.03%, respectively, and their 90% confidence intervals (CIs) were consistent with the range of 80.00%–125.00%, indicating that the two formulations had similar pharmacokinetics. Meanwhile, safety results showed that both drugs were well tolerated. Conclusion: Studies have shown that the test drug has similar bioequivalence and safety to the reference drug. Clinical trial registration: (http://www.chinadrugtrials.org.cn/index.html), identifier (CTR20171303).